Tongue coating index as a risk factor of decline of taste sensitivity in the elderly population - Fimma Naritasari; Dewi Agustina; Fania Chairunisa; Lisdrianto Hanindriyo; Elastria Widita; Iffah Mardhiyah (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
The elderly had various oral health issues, one of which is taste sensitivity. Taste sensitivity is highly affected by a person’s health, medication, eating habits, nutritional status, and oral hygiene. As an important organ for the sense of taste, the tongue can be covered in a white coating of debris, bacteria, and dead cells. To clean the tongue coating, one can do tongue brushing procedure, but this practice is not common among the elderly, especially in Indonesia. This cross-sectional study involved 114 older adults (n= 114) in the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta- DIY), Indonesia, who were selected using stratified random sampling. The participants first signed the informed consent before undergoing an interview and going through oral clinical examination. This research particularly measured the tongue coating index and taste sensitivity level by way of statistically analyzing both variables to determine the correlation between tongue coating index and taste sensitivity level using three-dropmethod. Data from 114 subjects were presented descriptively using table and graphic. Most of the subjects 90.53% (103 subjects) had a coated tongue with various degree. The correlation statistic between tongue coating index and taste sensitivity level showed the statistically significant correlation (p-value = 0.019) and the coefficient correlation was -0.216, which means that there was a negative and weak correlation between both. Elderly with a higher tongue coating index tended to have less taste sensitivity. This could be due to debris blocking taste buds, thereby reducing taste sensitivity.